Effects of different feed mills and conditioning temperature of pelleted diets on nursery pig performance and feed preference from 14 to 50 lb - De Jong, Jon A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 644 pigs (PIC 1050 or 327 × 1050, initial BW~14 lb) were used in 3 experiments to determine possible explanations for poorer pig performance in previous studies with pigs fed pelleted diets compared with those fed meal diets. Therefore, we examined feed pelleted from different mills as well as conditioning temperature as factors influencing our previous results. In Experiment 1, pens of pigs were randomly allotted to 1 of 3 dietary treatments with 10 pens per treatment and 7 pigs per pen. The 3 dietary treatments used the identical corn-soybean meal–based formulation and were mixed from the same batch of ingredients. Experimental diets were: (1) feed mixed at mill B but pelleted in mill A; (2) feed mixed and pelleted at mill B; and (3) feed mixed at mill B and fed in meal form. Experiment 2 was a feed preference study where pens of pigs were randomly allotted to the same diets as Experiment 1 with 4 pens per treatment and 7 pigs per pen. Pens contained 2 feeders, each containing 1 of 3 treatment diets. Feeders were rotated once daily within each pen for the entire 33-d study with three diet comparisons tested: 1 vs. 2, 1 vs. 3, and 2 vs. 3. In Experiment 3, pens of pigs were randomly allotted to 1 of 5 dietary treatments and fed for 16 d with 14 pens per treatment and 5 pigs per pen. Similar to Experiment 1, all diets used the identical corn-soybean meal–based formulation and were mixed from the same batch of ingredients. The experimental diets were: (1) feed mixed at mill A and fed in meal form; (2) feed mixed at mill A, but pelleted at mill B; (3), (4), and (5) feed mixed and pelleted at mill A at a conditioning temperature of 140, 160, or 180˚F, respectively. In Experiment 1, pigs fed the mill-B pelleted diet had the greatest (P < 0.05) ADG, whereas pigs fed the mill-A pelleted diet had the lowest (P < 0.05) ADG, with the meal diet from mill B intermediate (Table 6). There were no differences in ADFI among the three experimental diets. The mill-A pelleted diet significantly worsened (P < 0.05) F/G and final BW compared with the mill-B pelleted diet, whereas the mill-B mash diet only tended (P < 0.06) to worsen F/G compared with the mill-B pelleted diet. In Experiment 2 for comparison 1, pigs consumed more (P < 0.05) of the mill-B pelleted diet than the mill-A pelleted diet, which translated into pigs eating 70% of their daily intake from the mill B pellet (Table 7). For comparison 2 and 3, pigs fed either the mill-A or mill-B pellet consumed more feed (P < 0.05) than the mill B diet fed in mash form, with the pellets equated to 90% of their daily intake. For Experiment 3, there were no differences among the three diets pelleted under increasing conditioning temperatures at mill A, so they were combined for analysis (Table 8). Pigs fed the meal diet had improved (P < 0.05) ADG compared with pigs fed the mill-A pellet with the mill-B pellet fed pigs intermediate. For ADFI, both mill-B and mill-A pellet-fed pigs had reduced (P < 0.05) intake compared with the meal diet but improved (P < 0.05) F/G. Final BW was reduced when pigs were fed the mill-A pelleted diet compared with the mash diet, with the pigs fed the mill-B pellet intermediate. In our study, conditioning temperature did not seem to explain the differences between mill-related growth performance differences observed in Experiments 1 and 2. More research is needed to fully elucidate the reason why pig performance may differ when the same feed is processed in different mills.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Feed preference; Conditioning temperature; Nursery pig; Pelleting